Identificação molecular e perfil sorológico de Leptospira spp. isolada de gambás-de-orelha-branca (Didelphis albiventris) no sul do Brasil - Jorge, Sérgio (2009)
Leptospirosis is a zoonotic disease that occurs all over the world, particularly in developing countries, caused by bacteria of the genus Leptospira. Several marsupial species are considered susceptible to infection caused by a wide variety of Leptospira serovars, acting as reservoirs. In this work were collected serum and urine samples of 33 White-eared opossum, trapped within distinct locations of Capão do Leão and Pelotas cities, in the South of Brazil, aiming to detect antibodies and to isolate leptospires. Serum samples were screened against a panel of 58 Leptospira spp and Leptonema illini serovars using the microscopic agglutination test (MAT). To attempt isolation, urine samples from all animals were inoculated in culture medium.EMJH enriched with 10% of supplement Difco® One pathogenic serovar was isolated after two months of inoculation, and is first isolate the country for this animal species and was characterized by PCR using primers for 16S and Lipl32 genes. The technique of partial sequencing of the rpoB gene was used to identify the genomic specie. The isolated strain belongs to the specie L. borgpetersenii, which along with L .interrogans are the main cause disease in humans. The isolate, was tested on MAT using dog, cattle and human sera. Cut off titer of 50 was used for domestic animal sera and 25 for human and opossum sera. Both human and animal sera presented agglutination on MAT to isolated strain corresponding to 3.3% (2/60), 28.33% (17/60) and 1.67% (1/60) in human, dog and cattle sera, respectively. The opossum sera presented 36.36% (12/33) of reaction. These findings suggest a probable white-eared opossum role in the maintenance of pathogenic Leptospira on the environment since low titer sera and urine elimination were observed. These animals could be important reservoirs of Leptospira serovars for human and domestic animals.